The diverse worlds of unemployed adults : consequences for leisure, lifestyle, and well-being - Havitz, Mark E. (Wilfrid Laurier University Press, 2004)
Multi-method research study shows why leisure activities are as important for the unemployed as they are for the employed. Can someone who is unemployed experience leisure, or does that seem like a contradiction in terms? If unemployed people can experience leisure, how might it mitigate the negative effects of unemployment? And what form, then, would that leisure take? The relationship between leisure and unemployment has not received the attention it merits, especially in North America. Because research on leisure and unemployment must cross over areas of study, as well as theoretical perspectives, it can often seem conflicting and inconclusive. Yet the need for an understanding of that relationship remains. This groundbreaking book addresses that need. The authors describe the sometimes surprising results of their multi-method study of the effects of unemployment on leisure, lifestyle, and well-being within Canada, and integrate those results with literature collected worldwide into a comprehensive picture.; Using in-depth interviews, quantitative experience sampling, and standardised questionnaire data, this fascinating book provides ample evidence that the lived experiences of the unemployed are incredibly diverse, and the need for leisure is as intense for them as for the employed. The authors also pinpoint changes in public policy and social service agency management at local, provincial, and federal levels that will better serve unemployed people and their dependants, and enable them to use leisure activities to improve their lives.